Altering the availability or proximity of food, alcohol, and tobacco products to change their selection and consumption - Hollands, GJ; Carter, P; Anwer, S; King, SE; Jebb, SA; Ogilvie, D; Shemilt, I; Higgins, JPT; Marteau, TM (Wiley, 2019)
Background Overconsumption of food, alcohol, and tobacco products increases the risk of non‐communicable diseases. Interventions to change characteristics of physical micro‐environments where people may select or consume these products ‐ including shops, restaurants, workplaces, and schools – are of considerable public health policy and research interest. This review addresses two types of intervention within such environments: altering the availability (the range and/or amount of options) of these products, or their proximity (the distance at which they are positioned) to potential consumers.